Merit first, need and equality second: hierarchies of justice - Andreas Siemoneit (International Review of Economics, 2023)
The question of "Justice" still divides social research, moral philosophy, and public discourse. Three principles of distributive justice (allocation rules) occupy center stage in the debate: merit (equity, proportionality), need, and equality. Yet their relation remains diffuse, and current theory does not inform political practice. Here, we aim to develop a coherent picture with an interdisciplinary analysis. From an evolutionary point of view, the foundational principle of justice is reciprocity in social exchange (what corresponds to merit). But besides being just, justice must be effective, efficient, and communicable, thereby making justice rather a social bargain and an optimization problem. Social-psychological insights (intuitions, rules of thumb, self-bindings) can inform us when and why the two allocation principles need and equality are more likely to succeed than merit would. But both are governed by reciprocal considerations, and self-bindings help to interpret altruism as "very generalized reciprocity." Regarding politics, the reciprocal social norm Meritocratic Principle can be implemented, and its controversy avoided, by concentrating on "non-merit," i.e., institutionally draining the wellsprings of undeserved incomes (economic rents). Avoiding or taxing away economic rents is an effective implementation of justice in market economies.
Keywords: D01; D63; D64; D72; D91; 330; Justice; Reciprocity; Meritocratic principle; Altruism; Self-binding; Economic rents